Research on the New Era Aesthetic Transformation of Traditional Chinese Arts and Crafts: The Cases Focusing on Glass Art - Zhi-hao, Sun (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2023)
Traditional craftsmanship maps out the Chinese philosophy of creation, but it has suffered during the rapid transformation of the aesthetic of industrialised, urbanised modernity. Glass art has a long history in China, but for a long time it has not been able to integrate deeply with science, but has existed as an imitation or substitute for nearby materials, so the several changes in glass art are closely linked to the entry of Western art into the Chinese art world, which is why it is defined as 'imported'. After the initial imitation of Western glass art, modern China has come to recognise the importance of its own cultural identity, which is at the heart of Eastern art's standing on the world stage and its dialogue with the world.